Egrova ljubljanska tiskarna in založba - Svoljšak, Sonja (2020)
The Ljubljana Eger family of printers and publishers was active from 1765 until 1873. The first member, Johann Friderik Eger, married the widow of printer Johann Georg Heptner in 1765 and took over the Heptner company. He printed official publications and books, textbooks, and newspapers in Latin, German, Italian, and Slovenian. He printed or published works of Linhart, Pohlin, Dev, as well as Vodnik's newspapers. After 1799, the printing press was run by his widow for some time. His son Johann Leopold (1773–1829), who learned the craft from his father, married the owner of former Merk’s printing press. After his mother's death in 1800, he probably united the two businesses. He was succeeded by his third wife Rosalia who ran the printing press until her death (1781). In 1873 her daughter Julijana leased the printing works to its long-time managers who eventually bought it off.The collection includes a selection of books and other prints by Johann Frederik, Maria Theresa, and Johann Leopold Eger from the National and University Library, the Ljubljana City Library, the Jože Udovič Public Library in Cerknica, and The Slovenian Museum of Natural History, which were suitable for digitization. It will be completed with later prints by Eger family.
The Ljubljana Eger family of printers and publishers were active from 1765 until 1873. The first member, Johann Friderik Eger (1735–1799), married the widow of printer Johann Georg Heptner, Maria Theresa in 1765 and took over the Heptner company. He printed books, textbooks, newspapers as well as official publications and other material in Latin, German, Italian and Slovenian. He for example printed or published Linhart's An attempt at the history of Carniola, Pohlin's Carniolan grammar, Dev's Pisanice, Linhart's Županova Micka, as well as Vodnik's Velika pratika, Mala pratika, and his Lublanske novize. He was also mayor of Ljubljana between 1782 and 1786. After 1799, the printing press was run by his widow for some time. Of the sons, only Johann Leopold (1773–1829), who learned the craft from his father, survived his parents. He became the head of Degotardi’s printing press after the death of Anton Degotardi, and married his widow Regina, who was also the owner of former Merk’s printing press. After his mother's death in 1800, he probably united the two businesses. He was succeeded by his third wife Rosalia (1788–1871), who ran the printing press until her death. She for example printed Navratil's Vedež and Vilhar-Levstik's Naprej. She was succeeded by her stepdaughter Leopoldina, and by her daughter Julijana, who leased the printing works to its long-time managers Anton Klein and Ivan Kovač in 1873. They eventually bought it off.The collection includes a selection of books and other prints by Johann Frederik, Maria Theresa and Johann Leopold Eger from the National and University Library, the Ljubljana City Library, the Jože Udovič Public Library in Cerknica, and The Slovenian Museum of Natural History, which were suitable for digitization. It will be completed with later prints by individual members of the Eger family, especially by the extensive opus of Johann Leopold's third wife, Rosalia Eger.
Keywords: 18./19. st.; Kranjska; Ljubljana; tiskarji; založniki